2018
DOI: 10.1002/chem.201803298
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Study on the Cycloreversion of a Nucleobase‐Derived Azetidine by Photoinduced Electron Transfer

Abstract: Azetidines are interesting compounds in medicine and chemistry as bioactive scaffolds and synthetic intermediates. However, photochemical processes involved in the generation and fate of azetidine-derived radical ions have scarcely been reported. In this context, the photoreduction of this four-membered heterocycle might be relevant in connection with the DNA (6-4) photoproduct obtained from photolyase. Herein, a stable azabipyrimidinic azetidine (AZT ), obtained from cycloaddition between thymine and 6-azaura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…14). 36 Relying on either direct or acetone-sensitized excitation, the desired azetidine (44) was isolated in 80-85% yield. Notably, the imine 43 used in this report did not require any conjugating group for successful reactivity.…”
Section: Intramolecular [2 + 2] Photocycloadditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…14). 36 Relying on either direct or acetone-sensitized excitation, the desired azetidine (44) was isolated in 80-85% yield. Notably, the imine 43 used in this report did not require any conjugating group for successful reactivity.…”
Section: Intramolecular [2 + 2] Photocycloadditionsmentioning
confidence: 99%
“…In a subsequent study, the Miranda group reported that the azetidine fragmentation could be achieved by both single-electron reduction and oxidation. 44 …”
Section: Scope and Limitationsmentioning
confidence: 99%
“…The impact of the solvation and the influence of the temperature and entropic effects on the kinetics and thermodynamics of the ring-opening reactions can be assessed with the data compiled in Table 3 and Table 4 , referring to the electronic thermodynamics (ΔE), the electronic activation energy (ΔE ‡ ), their respective corrected values with the zero-point vibrational energy (ZPVE), i.e., ΔE 0 and ΔE 0 ‡ , and the Gibbs free energies (ΔG and ΔG ‡ ). Note that the DFT protocol used here was previously validated by comparing to data generated at the CASPT2 level [ 15 ]. Commented above, the ΔE values indicate that both isomers undergo a spontaneous ring-opening reaction in the anionic state, while the same process in the cationic state is clearly endergonic.…”
Section: Resultsmentioning
confidence: 99%
“…The instability of the formed four-membered ring oxetane/azetidine intermediates is an important limitation because it prevents not only their isolation and characterization but also their use as substrates to investigate the electron-induced cycloreversion. Several models have been designed to mimic this intermediate to follow the electron-transfer processes by spectroscopic techniques [ 14 , 15 ] and theoretical methods [ 6 , 15 ]. Understanding DNA repair processes is crucial to comprehend not only life functioning and evolution on Earth, but also to develop applications that could contribute to the fight against the harmful biological consequences of unprotected exposure to solar radiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation